NEW TRENDS OF TEACHING ENGLISH AS FOREIGN LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article discusses new trends of teaching English as foreign language. It also deals with Modern pedagogical technologies which are not only the use of technical teaching aids or computers, it is the identification of principles and the development of methods for optimizing the educational process that increase educational efficiency.